Developing Educational philosophy in Accordance with comprehensive quality criteria - Shareef, Nadaw Mohammed M.; Muhi-Aldeen, Sarmad Salah (Al-Adab Journal, 2021)
The current research aims at studying developing educational philosophy in accordance with comprehensive quality criteria. In order to fulfill this aim, the researchers have conducted the analytical descriptive method that depends on analyzing the literature of comprehensive quality concept and the development of educational philosophy concept. The research is divided into four sections; section one sheds light on the problem and its significance, the aims, the value, and the definition of basic terms. In section two, the researchers have explained thoroughly the concept of educational philosophy and its importance, as well as they explained the efficiency of the educational institutions. Comprehensive quality criteria and measurement quality criteria in the educational process have been tackled in section three. Additionally, the advantages and applications of comprehensive quality criteria in the educational institutions has been already displayed. The focus of section four is on the adjustment of the quality of educational philosophy and the application of comprehensive quality criteria and how it is possible to develop the educational philosophy in accordance with comprehensive quality criteria. It has been concluded that the quality in the educational philosophy pave the way to make a comprehensive plan to develop the educational philosophy and the teaching process. Thus, in order to achieve such an aim there should be an integrated and interaction relationship between the human and political resources as well as the systems, curriculum, and the infrastructure to create efficient environment for creativity and innovation.